A novel pH-responsive hollow mesoporous silica nanoparticle (HMSN) system encapsulating doxorubicin (DOX) and glucose oxidase (GOX) for potential cancer treatment. Issue 20 (30th April 2019) - Cheng, Kaiwu; Zhang, Yu; Li, Yaojia; Gao, Zhiguo; Chen, Fanghui; Sun, Kai; An, Peijing; Sun, Chen; Jiang, Yong; Sun, Baiwang
Abstract : The multi-therapy modality is based on the combination and synergy of multiple single treatment modalities and materials chemistry. Abstract : The multi-therapy modality is based on the combination and synergy of multiple single treatment modalities and materials chemistry. Herein, a novel pH-responsive doxorubicin (DOX) delivery system based on hollow mesoporous silica nanoparticles (HMSNs) was constructed, which was designed to treat cancer via synergistic chemotherapy and starvation therapy. Logically, starvation therapy could improve the therapeutic efficiency by sensitizing the drug molecules and activating the chemotherapy; glucose oxidase (GOX) coupled to the surface of HMAN deprived the cancer cells of glucose for starvation therapy and increased the abnormality of the tumor microenvironment by locally reducing the pH, aggravating hypoxia and promoting the concentration of poisonous H2 O2 . Increased acidity could accelerate the depolymerization of pH-sensitive polyelectrolyte multilayers (PEM) wrapped on the most external surface, causing the spatial control of DOX release within tumor cells. Detailed physical characterization certified the successful synthesis of DOX/GOX@HMSN-PEM, which was approximately 180 nm in diameter. In vitro experiments demonstrated that GOX could effectively promote drug release, and DOX/GOX@HMSN-PEM possessed high drug loading rate and stability. Excellent cellular uptake performances were revealed by confocal laser scanning microscopy (CLSM). The positively charged nanoparticles could specifically target the cancer cells overexpressing negative charges. In addition, they were found to have an excellent effect on the cytotoxicity and apoptosis. The promoted drug release via combined starvation therapy and drug therapy suggests that this novel type of pH-responsive hollow mesoporous silica nanoparticles may serve as a new drug delivery system for cancer treatment.